2023
DOI: 10.1590/1807-3107bor-2023.vol37.0016
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing of oral epithelial dysplasia samples reveals an association with new genes

Abstract: The genetic basis of oral epithelial (OED) is unknown, and there is no reliable method for evaluating the risk of malignant transformation. Somatic mutations are responsible for the transformation of dysplastic mucosa to invasive cancer. In addition, these genomic variations could represent objective markers of the potential for malignant transformation. We performed whole-exome sequencing of 10 OED samples from Brazilian and Chilean patients. Using public genetic repositories, we identified 41 deleterious var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…In our study, we observed EGFR overexpression in 56.3% of cases, and we also showed that high EGFR expression tends to be associated with tumors with grade III of malignancy. This aligns with research in human oral [65][66][67] and cutaneous squamous cell carcinomas [68]. The association between EGFR immunoexpression and the degree of malignancy is also consistent with previous studies on several canine cancer [69,70].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we observed EGFR overexpression in 56.3% of cases, and we also showed that high EGFR expression tends to be associated with tumors with grade III of malignancy. This aligns with research in human oral [65][66][67] and cutaneous squamous cell carcinomas [68]. The association between EGFR immunoexpression and the degree of malignancy is also consistent with previous studies on several canine cancer [69,70].…”
Section: Discussionsupporting
confidence: 91%
“…Changes in some genes have been identified in oral epithelial dysplasia that may contribute to modifications in the tumor microenvironment of leukoplakia, such as in FAM198B ( 56 ). A positive correlation has been determined between FAM198B and the infiltration of major immune cells (including macrophages, Treg, and NK cells), and this gene has been suggested as a promising therapeutic target to reverse gastric cancer ( 57 ).…”
Section: Leukoplakia-infiltrating Leukocytes (Lils)mentioning
confidence: 99%
“…Understanding their interactions with dysplastic cells, such as antigen presentation or immune suppression, is critical to unraveling the early events in oral cancer development and holds promise for improved diagnostic approaches. Changes in some genes have been identified in oral epithelial dysplasia that may contribute to modifications in the tumor microenvironment of leukoplakia, such as in FAM198B (56). A positive correlation has been determined between FAM198B and the infiltration of major immune cells (including macrophages, Treg, and NK cells), and this gene has been suggested as a promising therapeutic target to reverse gastric cancer (57).…”
Section: Interaction Between Oral Dysplasia and Microenvironmentmentioning
confidence: 99%